Comparison of the Prevalence of Geographic Tongue in Asthmatic Patients and Healthy Subjects in Masih Daneshvari Hospital in 2014 - S Lesan; N Goudarzi; H Heidarnezhad; M Hassan Galyaie (Islamic Azad University, 2017)
Background and aim: Geographic tongue is a recurrent disorder with several associated etiologies. It is believed to be a common occurrence in the patients suffering from recurrent, acute inflammatory diseases. The purpose of this study was to compare the prevalence of geographic tongue between asthmatic patients and healthy subjects. Materials and Methods: This descriptive-analytic study was conducted on 80 asthmatic patients and 80 healthy controls. The asthmatics were selected from among the patients presenting to Masih Daneshvari hospital with a confirmed diagnosis of asthma, while the healthy controls were selected from among patients' companions. The case and control subjects were matched according to age, sex and cigarette smoking status. The presence of geographic tongue was evaluated in the subjects by clinical examination and also by using a questionnaire. The data were entered into SPSS software version 22 and were evaluated using Chi-Square test. Results: The prevalence of geographic tongue was 21.2% (n=17) in the asthmatic patients and 5% (n=4) in the healthy controls. A significant association was found between asthma and occurrence of geographic tongue (P<0.002). The incidence of geographic tongue in the asthmatics was 4.2 times greater than that in the healthy individuals with a relative risk (RR) equal to 4.2 and an attributable risk (AR) of 16%. In both groups, the dorsal and lateral surfaces of the tongue were more commonly affected than the ventral surface. No significant association was found between the involvement of a specific tongue surface and asthma (P=0.748). Conclusion: According to the results, the asthmatic patients showed a significant higher prevalence of geographic tongue compared with the healthy controls.